SOCIO-POLITICAL DISINTEGRATION AND DOMESTICATION OF THE NOVEL IN AFRICA: A READING OF BINWELL SINYANGWE’S A COWRIE OF HOPE - ADOKI Kemealo (Ziglôbitha)
Abstract: Using Sociocriticism and Semiotics, this work has shown that language’s evolvement has not been only in the distant past. The common understanding of the words’ meanings is ever changing and we make conscious, rational decisions about which words to use and what to mean by them in order to fit local culture. Binwell Sinyangwe’s choice of words in A Cowrie of Hope is a means to make sense in a selection event. This crafting of language casts human cultural and linguistic evolution. This work has shown how the novelist expresses some realities that are particular to African context in general and to Zambia culture in particular. Moreover, it has examined the literary construction with a hybrid language reflected in the text. The two theories shed light on the dynamic integration process with ideological traces and antagonistic tensions between social classes. Out of this study, it has revealed the human private lives and public character and helped rethink how domestication can bridge the gap for the hope of a new Africa. Keywords: Africa, change, domestication, language, local culture,